Noncognitive Skills, Internet Use and Educational Dropout - Katja Coneus; Johannes Gernandt; Marianne Saam (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2008)
Using data from the German Socio-Economic Panel for the years 2000 to 2006 we analyze the determinants and labor market effects of educational dropout. In addition to classical variables like family background and occupation, we examine noncognitive skills and Internet use. Noncognitive skills and Internet availability at home are negatively associated with the probability of becoming an educational dropout. The wage gap between dropouts and those with completed school and professional education vanishes for males once we control for additional characteristics such as occupations, professional Internet use and noncognitive skills. For females it is reduced to four percent.
Keywords: O30; I21; J31; 330; education; unemployment; wages; noncognitive skills; computer use; Abbrecher; Kognition; Qualifikation; Internet; Computergestütztes Verfahren; Bildungsertrag; Deutschland